Age-based double EWMA controller and its application to CMP processes - Chen, A.; Ruey-Shan Guo (IEEE transactions on semiconductor manufacturing, 2001)
In the originally proposed run-by-run control scheme, the EWMA statistic is used as an estimate of the process deviation from its target. However, the controller based on the EWMA statistic is not sufficient for controlling a wearing out process. The PCC controller has been thus proposed to enhance the run-by-run controller capability. In this paper, we first reexamine the fundamentals of the PCC formulations and propose an adjustment that is advantageous in controlling processes subject to both random shifts and drifts. The adjusted PCC controller is then further refined to take into account the process age. This age-based double EWMA scheme is then applied to the CMP process, which is known in the semiconductor industry to be rather unstable.